Internal Conflict of Laws in Iraq "Analytical Study" - Rahim, Bakhtiar Siddiq (Journal of Legal and Political Studies, 2025)
Iraq is a federal state, and the Kurdistan Region is independent with its own laws, which leads to the emergence of a conflict between federal laws and regional laws, which requires legal contexts to resolve this conflict and determine the applicable law to the disputes that arise, by benefiting from the established rules in the conflict and its historical roots, and the judge must follow certain standards for the chosen solution, which are multiple standards, and in order for the judge to be able to reach these solutions, there must be specific standards in the law, to be taken into account, especially since the rules that came with the civil law do not help the judge in finding a solution, because those rules were established to resolve international conflicts of laws, without internal conflicts, which cannot be bypassed in federal states, and Iraq as a case study, Therefore, through this research, we presented the problems of this issue and provided appropriate solutions for them. Keywords: internal conflict, regionalism of laws, personality of laws, regionalism criterion, sectarianism criterion.
Keywords: internal conflict; regionalism of laws; personality of laws; regionalism criterion; sectarianism criterion